Mitochondrial RNA in Alzheimer’s Disease Circulating Extracellular Vesicles - Kim, Kyoung Mi; Meng, Qiong; Perez de Acha, Olivia; Mustapic, Maja; Cheng, Aiwu; Eren, Erden; Kundu, Gautam; Piao, Yulan; Munk, Rachel; Wood, William H.; De, Supriyo; Noh, Ji Heon; et al. (Frontiers in Cell and Developmental Biology, 2020)
Alzheimer's disease (AD) is the most common type of dementia. Amyloid β (Aβ) plaques, Tau-containing neurofibrillary tangles, and neuronal loss leading to brain atrophy are pathologic hallmarks of AD. Given the importance of early diagnosis, extensive efforts have been undertaken to identify diagnostic and prognostic biomarkers for AD. Circulating extracellular vesicles (EVs) provide a platform for ‘liquid biopsy’ biomarkers for AD. Here, we characterized the RNA contents of plasma EVs of age-matched individuals who were cognitively normal (healthy controls, HC) or had Mild Cognitive Impairment (MCI) due to AD or had mild AD dementia (AD). Using RNA sequencing analysis, we found that mitochondrial (mt) RNAs, including MT-ND1-6, and other protein-coding and noncoding mt-RNAs, were strikingly elevated in plasma EVs of MCI and AD individuals compared with HC. EVs secreted from cultured astrocytes, microglia, and neurons after exposure to toxic conditions relevant to AD pathogenesis (Aβ aggregates and H2O2), contained mitochondrial structures (detected by electron microscopy) and mitochondrial RNA and protein. We propose that in the AD brain, toxicity causing mitochondrial damage results in the packaging of mitochondrial components for export in EVs, and further propose that mt-RNAs in plasma EVs are robust diagnostic and prognostic biomarkers for AD.